Neoliberalism, Pedagogy and Human Development : Exploring Time, Mediation and Collectivity in Contemporary Schools. - Kontopodis, Michalis (Routledge research in education., 2012)
In most Western developed countries, adult life is increasingly organized on the basis of short-term work contracts and reduced social security funds. In this context it seems that producing efficient job-seekers and employees becomes the main aim of educational programs for the next generation. Through case studies of young people from urban and countryside marginalized populations in Germany, USA and Brazil, this book investigates emerging educational practices and takes a critical stance towards what can be seen as neoliberal educational politics. It investigates how mediating devices such.